2021
DOI: 10.5194/acp-21-14941-2021
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the surface temperature response and its uncertainty to CO<sub>2</sub>, CH<sub>4</sub>, black carbon, and sulfate

Abstract: Abstract. Understanding the regional surface temperature responses to different anthropogenic climate forcing agents, such as greenhouse gases and aerosols, is crucial for understanding past and future regional climate changes. In modern climate models, the regional temperature responses vary greatly for all major forcing agents, but the causes of this variability are poorly understood. Here, we analyze how changes in atmospheric and oceanic energy fluxes due to perturbations in different anthropogenic climate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…2a). Our results are consistent with Nordling et al (2021) who show the higher sensitivity to non-CO2 forcing compared to CO2 forcing (Figure S4).…”
Section: Climate Impactssupporting
confidence: 93%
See 1 more Smart Citation
“…2a). Our results are consistent with Nordling et al (2021) who show the higher sensitivity to non-CO2 forcing compared to CO2 forcing (Figure S4).…”
Section: Climate Impactssupporting
confidence: 93%
“…This physiological warming occurs because plants close their stomata under elevated CO2, reducing transpiration and decreasing latent heat loss which causes a local surface warming. Nordling et al (2021) further demonstrated that change in top of the atmosphere (TOA) long-wave clear-sky emissivity is the key driver for the temperature response differences between GHGs forcings. Using Earth System model simulations, Tokarska et al (2018) showed that non-CO2 forcing reduces the remaining carbon budget due to its direct radiative effects on surface temperature, causing additional warming.…”
Section: Introductionmentioning
confidence: 99%
“…A shift from high α when black carbon dominates (around 1925) to low α as sulphates become more important (1950 onwards) would be consistent with the finding by Ceppi and Gregory (2019) of larger α (lower sensitivity) from black carbon than sulphate forcing. This is an uncertain explanation, however, as other works found opposite results (Nordling et al., 2021; Richardson et al., 2019). Furthermore, feedbacks remain closer to the value from regression across the full period after forcing becomes more significant ( i .…”
Section: Time‐evolution Of Radiative Feedbackmentioning
confidence: 81%